O diagnóstico médico à luz do pragmatismo e da semiótica de Peirce - Bueno, José Geraldo Romanello (2023)
This paper intends to defend the thesis that medical professionals, even without knowing it, use in their diagnostic processes a structure accustomed to the general movement of the scientific spirit, which seeks the explanation of general observable facts, namely, the logical-objective structure based on the forms of reasoning: abduction, deduction and induction. Being aware of this process as a whole and, above all, of the essential role that abduction plays in it due to its heuristic and instinctive role becomes a qualitative differential for the fulfillment of the purposes of medicine. Semiotics, the science of signs, occupies a prominent place in the philosophy of Charles Sanders Peirce. In this context, the semiotics of medical diagnosis can be considered a practical application of his theories, having significant implications for the way we understand and practice medicine. According to Peirce, every thought is in some way a sign, and in Medicine, symptoms are the signs that doctors interpret to arrive at a diagnosis of a disease and propose treatment. The process of medical diagnosis can be seen as an interpretive process that aligns with Peirce's abductive logic, in which the physician, based on a series of symptoms (signs), infers the best possible explanation (diagnosis). In this way, Peircian semiotics offers a valuable philosophical contribution to Medicine, demonstrating that diagnosis is both a scientific process and an interpretative act, which leads to a more holistic and humanized approach to medical practice. The research was developed using a qualitative, hypothetical-deductive methodology, based on analysis of primary and secondary literature on Peircian semiotics and abduction in order to make a medical diagnosis possible. Books (doctrine), specialized journals, theses, monographs and book chapters were also used in this research. It was concluded that Peircian semiotics and abduction have full relevance and usefulness in the field of medical diagnosis. The semiotics approach has provided a conceptual framework that helps to understand the complexity of medical diagnoses. The language of signs and symptoms in medicine is complex and requires a careful approach on the part of the physician. Semiotic dialogue is an essential tool where, through the use of signs, physicians are able to discuss, interpret and communicate complex health information, allowing them to make an accurate, fair and effective diagnosis of the pathologies that affect their patients so that they can design the correct treatment. In addition, it is indispensable, in order to achieve this goal, that the doctor has a solid knowledge of the different types of signs and symptoms that may occur with each pathology that the doctor encounters. Finally, the understanding of the semiotics of medical diagnosis and its abduction is fundamental for medical training and education and, consequently, the improvement of current diagnostic and therapeutic practices, which are unfortunately so scarce today